Effect of age, season, and gender on bronchoalveolar lavage fluid cytology in camels - Mohamed Ali Al-Ali; Turke Shawaf (Open Veterinary Journal, 2023)
Background: Bronchoalveolar lavage fluid (BALF) samples are valued mirrors of different parts of the airway and can be used with other approaches to diagnosis of the lower respiratory tract. Several previous studies on various animal species showed the effect of the season, gender and age on the percentage of cells in the BALF samples. Aim: The main aim of this study was to determine the impact of gender, age, and season on the cytological analysis in BALF of dromedary camels. Methods: Thirteen healthy camels were involved in this study. Camels were selected based on general respiratory clinical scoring. BALF was done using a special BALF catheter. BALF samples were analyzed from dromedary camels by microscopic examination of prepared smears. Results: The results of the BALF cytology percentage revealed that there was no variation between winter and summer in most cell types. Only the mean value of neutrophil cell percentage in BALF in winter increased significantly (10.75±1.31) compared to summer (4.60±0.81). The range of eosinophils was in summer (0-13) wider than in winter (0-2). A significant difference was recorded in lymphocytes, eosinophils and epithelial cells percentage among adult and young camels. There was a high mean value of epithelial cells percentage in adult camels (10.17±1.64) comparing to young animals (3.0±0.58). The results of the BALF cytology among males and camel showed no significant difference. Conclusion: The present study revealed significant differences in the BALF cytology regarding age and season, but no impact on gender. [Open Vet J 2023; 13(5.000): 550-557]